THE LIGHT GRADIENTS INSIDE SOYBEAN LEAVES AND THEIR EFFECT ON THE CURVATURE FACTOR OF THE LIGHT RESPONSE CURVES OF PHOTOSYNTHESIS - TANIA JUNE (BIOTROPIA, 2005)
ABSTRACTÂ  Light gradients within leaves are not included in the model of Farquhar, although a steep light gradient does exist within leaves. For a bifacialÂ  leaf, the model shows good agreement with measured data, but for an isobilateral leaf the model may underestimate photosynthesis measured by conventional gas exchange. Isobilateral leaves easily developed when plants were grown in growth chambers where some light were reflected from the growth chamber metal base onto the lower surface of the leaves during growth, resulting in adjustment of the photosynthetic capacity inside the leaves. This could also happen in theÂ  field when canopy is very sparse and lower surface of leaves was exposed to reflected light from soil surface.Â  Complications occurred when fitting the light response curves of the electron transport rate, due to the interaction between the quantum yield of electron transport (a2) and the curvature factor (Î˜). It is suspected that there may be an interaction with the light gradientÂ  within the leaf. This manuscript discusses the effect of a light gradient inside a soybean leaf on the estimation of Î˜. It is shown in the manuscript how the light curves of the isobilateral leaves (at different degree) responded when measured using conventional gas exchange andÂ  how it affected the estimation ofÂ  Î˜ and the electron transport capacity, Jmax. An experiment was conducted to prove the hypothesis that this â€œout of ordinaryâ€ estimate of Î˜ (and hence Jmax) was due to the unmatched distribution of photosynthetic capacity with distribution of absorbed light.Â  Â Keywords :Â  light gradient / photosynthetic capacity (Jmax) / curvature factor (Î˜) / gas exchange Â Â